Empowerment of Kelompok Wanita Tani (KWT) Amanah, Sidomulyo in Ecoprint Making - Aji, Oktira Roka; Pratiwi, Ambar (Research Collaboration Community (RCC), 2024)
Sidomulyo Village, situated in Bantul Regency, Indonesia, is confronted with economic challenges, particularly among its predominantly female population who face limited educational and economic opportunities. Recognizing the village's abundant natural resources, this community service program facilitated by Kelompok Wanita Tani (KWT) Amanah aimed to empower local women through ecoprint batik making. The program focused on equipping participants with skills in ecoprint techniques using locally sourced plant materials. Through stages of socialization, training, mentoring, and evaluation, the participants learned to create vibrant fabric patterns without chemical dyes, promoting environmental sustainability and preserving local biodiversity. Positive feedback highlighted the program's effectiveness in enhancing participants' skills and knowledge, with a strong interest shown in further developing ecoprint skills and exploring entrepreneurial opportunities, including online marketing. This study underscores the transformative impact of community-based initiatives in promoting women's economic independence and sustainable development through traditional craft practices.